Critical Review of Spaylater Practices of LPI Educators. Darul Ulum Banyuanyar Putri Maqasid Dain Jasser Auda Perspective - Rohmatun Shomad; Salma Mansur (Amkop Management Accounting Review (AMAR), 2025)
Along with the rapid development of the times, buying and selling practices are increasingly easy to do through fintech (Financial Technology) in the form of shopee. Shopee is an application that serves buying and selling and also accounts payable online. Debt and credit services using Shopee in the form of Shopee payLater (SpayLater) or pay at a later date which is currently in great demand by all groups including educators because it can help buy the desired item at any time without thinking about financial conditions. This study aims to analyze the practice of debt carried out by LPI teachers. Darul Ulum Banyuanyar daughters on the Shopee application through SpayLater in terms of maqasid shari'ah thought of Jasser Auda. This research uses field research with a comparative descriptive approach to maqasid shari'ah Jasser Auda. The research results that, First, Maqashid dain in QS. Al-Baqarah: 282 maqashid syaria'ah Jasser Auda's perspective gave birth to the concept of recording (faktubuu) and testimony (fasytasyhiduu), Second, Spaylater Practices Among LPI Educators. Darul Ulum Banyuanyar Putri Based on Maqashid Dain Jasser Auda uses 6 system features, namely: cognitive nature, wholeness, openness, interrelated hierarchy, multidimensionality, and purposefulness, as well as the maintenance of human rights (hifdz al-huquq al-insan), maintenance of human dignity (hifdz al-'ird), and maintenance of property (hifdz al-mal).